Penerapan Teknologi Forged Carbon Compression Split Moulding (FCCSM) untuk Mendukung Industri Hijau dan Zero Waste pada UKM Komponen Berbahan Karbon Fiber - Roziqin, Ahmad; Hapsoro, Bayu Bagas; Rohman, Shohihatur (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
The use of carbon fiber (carbon fiber reinforced plastic) in the automotive component industry produces significant waste, reaching 15-20% of the total raw materials. The community service partner, BPM Carbon Works Semarang, previously handled this waste by incineration, which caused environmental and economic problems. This community service program aims to address these problems through the application of Forged Carbon Compression Split Molding (FCCSM) technology. The methods used include lectures, demonstrations, hands-on practice, and assistance in designing two- and four-part split molds, as well as processing carbon fiber waste into commercially valuable products. The results of the activity show that the amount of partner waste is reduced from 20% to 5%, and partner understanding increases significantly with N-Gain scores of 0.73 and 0.75 (high category). In addition, partner profits increase by 15%. This program not only solves environmental problems, but also empowers the partner's economy, in line with the achievement of sustainable development goals (SDGs). Thus, it can be concluded that FCCSM technology is effective in achieving a zero-waste industry, and ongoing mentoring and collaboration with local governments are recommended.